Wiggle and Shake: Managing and Exploiting Conformational Dynamics during Proteasome Biogenesis - Daniel Betancourt; Tomiwa Lawal; Robert J. Tomko (Biomolecules, 2023)
The 26S proteasome is the largest and most complicated protease known, and changes to proteasome assembly or function contribute to numerous human diseases. Assembly of the 26S proteasome from its ~66 individual polypeptide subunits is a highly orchestrated process requiring the concerted actions of both intrinsic elements of proteasome subunits, as well as assistance by extrinsic, dedicated proteasome assembly chaperones. With the advent of near-atomic resolution cryo-electron microscopy, it has become evident that the proteasome is a highly dynamic machine, undergoing numerous conformational changes in response to ligand binding and during the proteolytic cycle. In contrast, an appreciation of the role of conformational dynamics during the biogenesis of the proteasome has only recently begun to emerge. Herein, we review our current knowledge of proteasome assembly, with a particular focus on how conformational dynamics guide particular proteasome biogenesis events. Furthermore, we highlight key emerging questions in this rapidly expanding area.